2021
DOI: 10.3390/molecules27010170
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Clay Soils against Food-Borne Salmonella typhimurium and Staphylococcus aureus

Abstract: Natural clays have recently been proven to possess antibacterial properties. Effective natural antimicrobial agents are needed to combat bacterial contamination on food contact surfaces, which are increasingly more prevalent in the food chain. This study sought to determine the antibacterial activity of clays against the food-borne pathogens Salmonella Typhimurium ATCC 14028 and Staphylococcus aureus ATCC 13565. Soils were processed to yield leachates and suspensions from untreated and treated clays. Soil part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The raw Sm and Sm/Dye did not show antimicrobial activity against S. aureus, L. monocytogenes, and C. albicans, and showed a low potential against E. coli. Azmi et al [47] reported the antibacterial activity of clays was not uniform due to differences in mineralogical and geochemical composition. The antibacterial activity of clay leachates was The color difference (∆E) obtained from the values of the L*, a*, and b* parameters for the new pigments before and after light exposure is shown in Figure 7b.…”
Section: Hybrid Pigments-antibacterial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw Sm and Sm/Dye did not show antimicrobial activity against S. aureus, L. monocytogenes, and C. albicans, and showed a low potential against E. coli. Azmi et al [47] reported the antibacterial activity of clays was not uniform due to differences in mineralogical and geochemical composition. The antibacterial activity of clay leachates was The color difference (∆E) obtained from the values of the L*, a*, and b* parameters for the new pigments before and after light exposure is shown in Figure 7b.…”
Section: Hybrid Pigments-antibacterial Propertiesmentioning
confidence: 99%
“…This antibacterial property can be explained by the Cu 2+ ions released continually from Cu-Sm in contact with bacteria [52,53] by a mechanism that, in general, is a The raw Sm and Sm/Dye did not show antimicrobial activity against S. aureus, L. monocytogenes, and C. albicans, and showed a low potential against E. coli. Azmi et al [47] reported the antibacterial activity of clays was not uniform due to differences in mineralogical and geochemical composition. The antibacterial activity of clay leachates was widely reported in the scientific literature and attributed to metal ion toxicity released from the clay mineral interlayer.…”
Section: Hybrid Pigments-antibacterial Propertiesmentioning
confidence: 99%
“…These findings emphasize the need to optimize formulations and concentrations to maximize the antibacterial activity of film materials for various applications, including food packaging and biomedical devices. Azmi et al (2022) provide insights into the various factors influencing the antibacterial properties of clay, which may be a significant avenue for future exploration if considering clay-based nanohybrids for antimicrobial applications [50].…”
Section: Antibacterial Properties Of Cs/pvoh/xac and Cs/pvoh/xto@ac F...mentioning
confidence: 99%
“…enterocolitica is frequently isolated from soil, water, and animals and can cause contamination in foods of all types [12]. It shares ecology with other bacteria such as Escherichia coli and is found in tropical and subtropical soils [13], Campylobacter jejuni is found in soil, roots, and shoots and causes gastroenteritis [14], Salmonella enterica causes contamination through the soil on which the plant is growing [15], Staphylococcus aureus is found in soil, water, and air and causes staphylococcal food poisoning [16], Clostridium perfringens is found frequently in soil, feces, and normal intestinal fl ora [17], Bacillus cereus is found in soil, vegetation, and food and causes intestinal illness with nausea, vomiting, and diarrhea; the soil is also the main habitat of Listeria monocytogenes and plays a pivotal role in the transmission of these bacteria from soil to plants and animals [18], and C. botulinum exists in soil, river, and sea and produces toxins in food.…”
mentioning
confidence: 99%